ARCHPRIEST AVVAKUM: THE FUSION OF TRADITIONS AND INNOVATION IN THE SYMBOLISM OF THE “LIFE” - Tsoy, Marina (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2024)
The article examines the transitional period of Russian literature of the XVII century, when important changes occurred in the system of genres and stylistic trends. Particular attention is paid to the process of confrontation between the traditional Byzantine orientation and new Western European influences. The key figure in the literature of that time is Archpriest Avvakum, whose "Life" is considered as a unique example of a combination of old and new literary traditions. Researchers note that although Avvakum did not strive to become an innovator, his works are distinguished by extraordinary expressiveness and originality. Analyzing the language and style of the "Life", the authors of the article point out a complex combination of canonical and colloquial elements and emphasize the significance of biblical quotations and symbols in the text. The article analyzes the symbolic system of "The Life of Archpriest Avvakum". The main attention is paid to the relationship between traditional symbols and the author’s imagery to discover particular details regarding the images embedded in the symbolism. The narrative of the Life unfolds in two planes - sacred and ordinary, which are traditional for medieval literature. The peculiarity of the text is the innovative combination of the heavenly and the earthly, which violates the established ancient Russian literary canon.